Cancer incidence and mortality in Chukotka, 1997–2010 - Dudarev, AA; Chupakhin, Valery; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2013)
Objectives. The general aim was to assess cancer incidence and mortality among the general population of Chukotka in 1997 2010 and to compare it with the population of Russia. Methods. Cancer data were abstracted from the annual statistical reports of the P.A. Hertzen Research Institute of Oncology in Moscow. The annual number and percent of cases, crude and age-standardized cancer incidence (ASIR) and mortality (ASMR) rates per 100,000 among men and women in the Chukotka Autonomous Okrug were determined for the period 1997 2010 for incidence and 1999 2010 for mortality. Two years’ data were aggregated to generate temporal trends during the period. In age-standardization, the Segi-Doll world standard population used by the International Agency for Research on Cancer was used. Results. The higher incidence and mortality rate of cancer (all sites combined) among men compared to women, which was observed in Russia nationally, was reflected also in Chukotka, although the difference between men and women was not statistically significant. Overall, the patterns of cancer sites are similar between Chukotka and Russia, with cancer of the lung/trachea/bronchus and stomach occupying the top ranks among men. Oesophageal cancer is common in Chukotka but not in Russia, whereas prostate cancer is common in Russia but not in Chukotka. Among women, breast cancer is either the commonest or second commonest cancer in terms of incidence or mortality in both Chukotka and Russia. Cancer of the lung/ trachea/bronchi ranks higher in Chukotka than in Russia. The rate of cancer incidence and mortality for all sites combined during the 13-year period was relatively stable in Russia. Dividing the period into two halves, an increase among both men and women was observed in Chukotka for all sites combined, and also for colorectal cancer. Conclusions. This paper presents previously unavailable cancer epidemiological data on Chukotka. They provide a basis for comparative studies across circumpolar regions and countries. With its small ...